E-GOVERNMENT SEMBAKODROID: ANDROID BASED APPS FOR MONITORING STAPLE FOOD - Ahmad Fahriyannur Rosyady; nfn Risnandar; Izzatul Ummah (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2015)
With the rapid development of technology, many people trying to catch up with that pace. This led many government agencies are utilizing technology, especially in the field of information technology to their business processes. So is Department of Industry and Trade of the Province of West Java, as an office that in charge of organizing and monitoring the flow of trade in West Java. Additionally,the institution has the task to monitor the price of nine basic (staple food) in the province of West Java. Currently, managing food prices can only be done by the admin in this case are employees of the institution. They have field officers who recorded the data directly from the market to get groceries price data. Then the data is sent to the admin and managed to put on the website. This has an impact on the length of time informing food prices to the public. Method development using SDLC with Prototype models. The application is divided into two : mobile applications and web applications that both use MySQL database. The Android mobile application platform that will be used by field personnel to input and process data reports food prices, PHP-based web application for creating document reports food prices. With the Android app for monitoring grocery prices based andoroid it will help employees to create data reports food prices in a timely manner. In addition, applications are built can be accessed by mobile field workers so that food prices data management processes can be performed directly in the market. Keywords: Food, Android, Web, Mobile